Evaluation of Some Purine Metabolism Enzymes in Iraqi type 1 Diabetic Patients - Wisam M. Mohammed (Journal of Global Pharma Technology, 2018)
Type 1 diabetes mellitus (T1DM) is the result of the destruction of the insulin-secreting β-cells of the pancreas by a process in which T-cells play a central role. This study was conducted on 60 T1DM patients from both sexes that were randomly selected from those attending the National Diabetes Center for Treatment and Research at Al-Mustansiriya University/Baghdad between August 2016 to December 2016. For comparison, 24 apparently healthy controls were selected for the control group. Moreover, the study was conducted to evaluate serum adenosine deaminase (ADA) and 5-nucleutidase (5-NT); furthermore, xanthine oxidase (XO) enzymes were quantitatively determined manually in T1DM patients and the control group. Fasting serum glucose (FSG), serum uric acid, urea, and total protein were determined, as well as other anthropometric measurements, such as body mass index (BMI);waist to hip ratio (W/H) and thoracic to hip ratio (T/H).The diabetic patients had significantly higher levels of ADA and 5-NT enzymes (p<0.000) compared with those of control group. No significant difference (p<0.463) was observed in the serum XO enzyme between the patients and the healthy control group. Further, the level of UA was significantly lower (p<0.000) in the patients compared with that of the healthy control group. This study suggests a significant role for ADA and 5-NT enzymes and a non-significant role for XO enzyme, which, therefore, cannot be used for predicting the progression of T1DM in the early stages.Keywords: Diabetes mellitus, Type 1 diabetes mellitus, Adenosinedeaminase enzyme, 5-Nucleutidase enzyme, Xanthineoxidase enzyme.